Desarrollo de una herramienta informática que permita realizar análisis de confiabilidad de redes en medio voltaje en sistemas de distribución - Chiliquinga Chanaluisa, Jeison Andres (2018)
The computer tool of management system focused on reliability (SISGEC), allows performing reliability index analysis established by the ARCONEL in the current regulation. (CONELEC 007/01), as TTIK, FMIK and ENS. For this purpose, SISGEC has the necessary resources that allow registering in a database the failure events and network interruptions with a subsequent analysis of the mentioned events to be able to determine the state of the electrical system at each point of the network, as well as at the feeder level. Additionally, the application has a special section with a geographic information system (GIS), where the components of the distribution network can be projected geographically as well as the information of the indexes previously calculated for the projected network component, it allows a more localized analysis that provides relevant information to the administrator who can plan a possible maintenance in the points of the network where the reliability indices are outside the limits allowed by the regulation. The importance of its performance in the reliability analysis support SISGEC provides alternatives in decision making for future planning.